Serotyping of non-cholera vibrios. - Smith, H L (1979)
The serotyping system for non-cholera vibrios reported by us in 1965 has been re-evaluated and extended. Results from serotyping 2,624 cultures are presented. These isolates were accumulated over a period of 20 years and came from clinical and environmental samples in many parts of the world. Included is a discussion of the use of terms "Vibrio cholerae" and "non-cholera vibrios" for clinical reports.